Injury risk in runners using standard or motion control shoes: a randomised controlled trial with participant and assessor blinding. Issue 8 (8th January 2016) - Malisoux, Laurent; Chambon, Nicolas; Delattre, Nicolas; Gueguen, Nils; Urhausen, Axel; Theisen, Daniel
Abstract : Background/aim: This randomised controlled trial investigated if the usage of running shoes with a motion control system modifies injury risk in regular leisure-time runners compared to standard shoes, and if this influence depends on foot morphology. Methods: Recreational runners (n=372) were given either the motion control or the standard version of a regular running shoe model and were followed up for 6 months regarding running activity and injury. Foot morphology was analysed using the Foot Posture Index method. Cox regression analyses were used to compare injury risk between the two groups, based on HRs and their 95% CIs, controlling for potential confounders. Stratified analyses were conducted to evaluate the effect of motion control system in runners with supinated, neutral and pronated feet. Results: The overall injury risk was lower among the participants who had received motion control shoes (HR=0.55; 95% CI 0.36 to 0.85) compared to those receiving standard shoes. This positive effect was only observed in the stratum of runners with pronated feet (n=94; HR=0.34; 95% CI 0.13 to 0.84); there was no difference in runners with neutral (n=218; HR=0.78; 95% CI 0.44 to 1.37) or supinated feet (n=60; HR=0.59; 95% CI 0.20 to 1.73). Runners with pronated feet using standard shoes had a higher injury risk compared to those with neutral feet (HR=1.80; 95% CI 1.01 to 3.22). Conclusions: The overall injury risk was lower in participants who had received motion control shoes. Based on secondary analysis, those with pronated feet may benefit most from this shoe type.